Catalytic Hydroisomerisation of Fischer–Tropsch Waxes to Lubricating Oil and Investigation of the Correlation between Its Physical Properties and the Chemical Composition of the Corresponding Fuel Fractions - Philipp Neuner; David Graf; Heiko Mild; Reinhard Rauch (Energies, 2021)
Due to environmental concerns, the role of renewable sources for petroleum-based products has become an invaluable research topic. One possibility of achieving this goal is the Fischer–Tropsch synthesis (FTS) based on sustainable raw materials. Those materials include, but are not limited to, synthesis gas from biomass gasification or hydrogen through electrolysis powered by renewable electricity. In recent years, the utilisation of CO2 as carbon source for FTS was one main R&D topic. This is one of the reasons for its increase in value and the removal of its label as being just exhaust gas. With the heavy product fraction of FTS, referred to as Fischer–Tropsch waxes (FTW), being rather limited in their application, catalytic upgrading can help to increase the economic viability of such a process by converting the waxes to high value transportation fuels and lubricating oils. In this paper, the dewaxing of FTW via hydroisomerisation and hydrocracking was investigated. A three phase fixed bed reactor was used in combination with a zeolitic catalyst with an AEL (SAPO-11) structure and 0.3 wt% platinum (Pt). The desired products were high quality white oils with low cloud points. These products were successfully produced in a one-step catalytic dewaxing process. Within this work, a direct correlation between the physical properties of the white oils and the chemical composition of the simultaneously produced fuel fractions could be established.